Treatment of cutaneous neurofibromas with carbon dioxide laser: Technique and patient experience - Peltonen Sirkku; Jannic Arnaud; Wolkenstein Pierre (Elsevier Masson s.r.l., 2025)
Cutaneous neurofibromas (cNF) are one of the hallmarks of neurofibromatosis 1 (NF1). The number of cNFs varies between individuals from a few to hundreds or even thousands and increases throughout adult life. cNFs cause a significant disease burden to adult patients and constitute an unmet need for therapy, since they may cause itch and pain and, being conspicuous and unsightly, stigmatize the patient. There is a lack of reports on how the outcome of various treatment options are perceived by the patients. Here we describe a technique for cNF removal using CO2 laser, and report how patients experience the procedure. Questionnaires were sent to patients who had had CO2 laser surgery in the French Referral Center for Neurofibromatoses, and in the Turku University Hospital, Finland, to retrospectively evaluate the patients’ global satisfaction of the procedure, treatment indications, and reasons for withdrawal from treatment, if this was the case. The number of returned questionnaires was 233/473 in France and 23/27 in Finland. The results showed that the most important indications for cNF removal were esthetic, and pain and itch caused by the tumors. In general, the procedure was well tolerated, and the degree of satisfaction was 8–10 on a scale from 0 to 10. For those 30% who discontinued the tumor removal program, the main reasons were organizational constraints, a non-satisfactory esthetic result, too many cNFs to treat, or problems with healing. Thus, the CO2 laser method is well tolerated but does not fully answer to the needs of the patients. Since medical treatment is not yet available, we encourage the use of laser removal of cNFs as a feasible method to decrease the tumor burden of the patients.